Andrology — what is it today? - M. I. Kogan (Вестник урологии, 2020)
The history of its appearance, development, formation is one of the «detectives» of medicine in the world and in Russia for the last 50 years. Everything developed in a very confusing, ambiguous, extremely controversial way. Andrology, having appeared, began to attract various specialists (urologists, endocrinologists, reproductologists, geneticists, gynecologists) and, of course, «medical politicians» and even pseudo-specialists — scammers. «Dark» spots in space and medicine have always fascinated the minds of the uninitiated. So, it was before our era, and so in modern times. I do not think that in this article I can afford to give a comprehensive interpretation of the whole complex of andrology problems, but I will try to draw the attention of the professional urological community of Russia to the key issues of the current moment.